2016
DOI: 10.1002/aoc.3559
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I) oxide nanoparticles supported on magnetic casein as a bio‐supported and magnetically recoverable catalyst for aqueous click chemistry synthesis of 1,4‐disubstituted 1,2,3‐triazoles

Abstract: Copper(I) oxide nanoparticles supported on magnetic casein (Cu2O/Casein@Fe3O4NPs) has been synthesized as a bio‐supported catalyst and was characterized using powder X‐ray diffraction, transmission electron microscopy, energy dispersive X‐ray and Fourier transform infrared spectroscopies, thermogravimetric analysis and inductively coupled plasma optical emission spectrometry. The catalytic activity of the synthesized catalyst was investigated in one‐pot three‐component reactions of alkyl halides, sodium azide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…In a recent related study, copper-catalyzed Huisgen azide-alkyne cycloadditions were conducted at room temperature to 70 °C and reaction time 3–12 h using water and alcohol as solvent to achieve high yield. The prepared Cu@Cu 2 O core-shell nanocatalyst provided the desired triazole with satisfactory conversion under similar mild reaction conditions [ 72 , 73 , 74 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a recent related study, copper-catalyzed Huisgen azide-alkyne cycloadditions were conducted at room temperature to 70 °C and reaction time 3–12 h using water and alcohol as solvent to achieve high yield. The prepared Cu@Cu 2 O core-shell nanocatalyst provided the desired triazole with satisfactory conversion under similar mild reaction conditions [ 72 , 73 , 74 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…The CS‐MCR/Cu 2 O was synthesized according to a previously reported method . CS‐MCR (1.00 g) was dispersed in water and then ultrasonication was performed at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…[187][188][189][190][191][192] Supported NPs offer several advantages over the use of unsupported NPs, such as better control of metal dispersion and particle morphology, inhibition of particle aggregation, and generally better reuse of the catalytic system. Given these attributes, different supported and recyclable CuNPs were employed in CuAAC reactions, among the supports employed are alumina, 193 aluminum oxyhydroxide, 194 montmorillonite, 195 MOF, [196][197][198] Cellulose, 199 SBA-15, 200 Zeolite, 201 and more recently graphene oxide. 202 In a study published in 2019 by Gholinejad et al 203 clinochlore was first reported as a very inexpensive and available support for the stabilization of copper nanoparticles and their application as a recyclable catalyst for the formation of 1H-1,2,3-triazoles at room temperature and in aqueous medium.…”
Section: Scheme 25mentioning
confidence: 99%